From Dolce Stil Novo to Dolce Vita: the perception of Italianness in a theater workshop for foreigners - Zingaro, Anna (Doświadczanie i wyrażanie włoskości: Aspekty językoznawcze i glottodydaktyczne, 2021)
This paper focuses on the potential of a theatre workshop to develop the communicative and cultural competence, the latter being related to the way Italianness is perceived by students of Italian as a Second Language. It first examines how a theatre workshop based on activities like constructing characters, dialogues and settings has proven useful in bringing into play the interpretive and imaginative skills of learners. Moreover, it shows how these activities allow learners to express their perception of the Italian culture through a mixture of both their literary and artistic education and a broader imaginary arising from the mass media, in particular from social networks and Italian songs. After illustrating the methodology adopted in the workshop, an overview of the Italian cultural references included in the theatrical texts staged will be provided, also envisaging a further development of this activity towards an ever greater cooperation between the students in the production of the theatrical text.